An Approach to Evaluation of the Effect of Bioremediation on Biological Activity of Environmental Contaminants: Dechlorination of Polychlorinated Biphenyls - Ganey, Patricia E. (National Institute of Environmental Health Sciences, 2005)
The effectiveness of bioremediation efforts is assessed traditionally from the loss of the chemical of interest. In some cases, analytical techniques are coupled with evaluation of toxicity to organisms representative of those found in the affected environment or surrogate organisms. Little is known, however, about the effect of remediation of environmental chemicals on potential toxicity to mammalian organisms. We discuss both an approach that employs mammalian cell system bioassays and the criteria for selection of the assays. This approach has been used to evaluate the biological response to mixtures of polychlorinated biphenyls (PCBs) before and after remediation by reductive dechlorination. The dechlorination process used results in accumulation of congeners substituted in only the ortho and para positions and containing fewer chlorines than the starting mixtures. Evaluation of the dechlorinated mixture reveals a loss of biological activity that could be ascribed to coplanar PCBs not containing chlorine in the ortho positions. Conversely, biological activity associated with ortho-substituted PCB congeners is unaffected or increased by remediation. Thus, the results of the bioassays are consistent with the remediation-induced change in the profile of PCB congeners and the known mechanisms of action of PCBs. The results emphasize a need for evaluation of the products of remediation for biological activity in mammalian systems. Furthermore, the approach outlined demonstrates the potential to assess the impact of remediation on a range of biological activities in mammalian cells and thus to estimate positive and negative effects of remediation strategies on toxicity. Future needs in this area of research include assays to evaluate biological effects under conditions of exposure that mimic those found in the environment and models to extrapolate effects to assess risk to people and wildlife.